Decreased Identification of Vesicoureteral Reflux: A Cautionary Tale - Qureshi, Aslam Hyder; Ajayi, Oluwaseun; Schwaderer, Andrew Lawrence; Hains, David S. (Frontiers in Pediatrics, 2017)
Aim: To find the trend in patient’s visits to our centers for vesicoureteral reflux. We hypothesize that VUR diagnosis and hence possible nephropathy recognition may be diminishing because of changing practice patterns. Methods: Data were extracted from electronic medical records for new and follow-up patients aged 0-18 years with ICD9/10 codes to correspond with VUR, VUR unilateral, VUR bilateral, and VUR with reflux nephropathy, as well as new patients with diagnoses of UTI and pyelonephritis at two major pediatric centers from 2012 to 2015. Figures and statistics to reflect absolute clinic visits and annual trends were created with SPSS 2010. Linear regression was applied. Results: Annually, Le Bonheur Children’s Hospital (LBCH) and Nationwide Children’s Hospital (NCH) experienced an average decrease of 13% and 17% in total VUR visits, and an average decrease of 22% and 27% in VUR nephropathy visits, respectively for each institution. Patient visits for UTIs were reduced an average of 16% annually in both centers. Linear regression demonstrated that number of patients (patients/year ± SE) decreased annually 69±19 (P= 0.02), 7±2 (P=0.02) and 67±25 (P=0.04) for VUR, VUR nephropathy and UTI, respectively. Conclusion: We conclude that the decrease number of VUR and VUR nephropathy cases identified in subspecialty clinics (Nephrology/Urology) at two major children’s hospitals reflect a possible decreased identification of VUR. This trend may also be due to decreased referral of low grade cases of VUR. We cannot conclude that “undifferentiated UTI” referrals increased concomitantly to account for the decreased VUR as our data reflects a decreased trend in those visits as well. We suggest that clinicians following the AAP guidelines ensure that all UTI are accounted for and surveillance is appropriately escalated for recurrent UTI or abnormal imaging results.